Pengaruh Jenis Bahan Bakar Terhadap Viskositas dan TBN Pelumas SAE10W-30 pada Motor Bakar 125cc - Dwi Yuliyanto; Edi Widodo (Universitas Muhammadiyah Sidoarjo, 2018)
Along with the increasing progress of gasoline type of fuel led to many types of gasoline fuel sold in Indonesia to meet consumer demand required for fuel energy motor fuel. Includes Premium fuel types, Pertalite, Pertamax, Pertamax Turbo, and Pertamax Racing. Therefore, with the number of options are conducted research on the use of 3 different types of fuel are: Premium, Pertalite, and Pertamax tested on a 125cc motor fuel engine for 7 hours nonstop at 4000 rpm speed to know the effect on the difference in decrease in value of Viscosity and TBN SAE10W-30 lubricating oil used on the combustion engine. Given the function Lubricant oil is also very important in maintaining the durability and performance of the engine. The results show that the use of Pertamax fuel has the highest decrease in Viscosity and TBN value compared to Pertalite and Premium fuels. Where each value of Viscosity and TBN on the sample of Pertamax lubricant 9.7 cSt and 6.9 mg KOH / g. Pertalite 9.8 cSt and 7.1 mg KOH / g. Premium 7.2 cSt and 10 mg KOH / g.